2016
DOI: 10.1002/ecs2.1252
|View full text |Cite
|
Sign up to set email alerts
|

A spatially‐explicit assessment of the fish population response to flow management in a heterogeneous landscape

Abstract: Ecological processes are structured in space and there are important benefits in incorporating spatial information for the analysis of data sets obtained from field studies. Assessing the effect of different flow management practices on river ecosystems is an example where such an exercise is highly relevant. Human activities such as hydroelectric power production are known to modify the temporal variability in river flow. Flow management strategies may have a direct influence on fishes and may trigger complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…). That result concurs partially with that of Guénard et al (), who found a negative impact of flow regulation by FS dams on total fish density. In contrast with that study, however, we found here that RR and ST dams seem to affect even more species than FS facilities.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…). That result concurs partially with that of Guénard et al (), who found a negative impact of flow regulation by FS dams on total fish density. In contrast with that study, however, we found here that RR and ST dams seem to affect even more species than FS facilities.…”
Section: Discussionsupporting
confidence: 92%
“…As a demonstration of the practical utility of the approach, we used phylogenetic habitat modelling to assess the effect of flow regulation by hydroelectricity production companies on fish species in rivers. That data set, had previously been used by Guénard et al (), who analysed the effect of water regulation on total fish density and species richness. Here it has been analysed in greater details to describe fish community structure in river sampled over a broad geographic range and make specific predictions for regulated sites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current velocity of a flowing body of water, such as a river, determines the spread of organisms and the availability of food sources for aquatic biota. The stronger the current velocity is, the greater the abundance of food sources is, which also leads to the better spread of fish, and ultimately affects population density (Hockley et al 2013;Guenard et al 2015).…”
Section: The Quality Of the Ciliwung River Watersmentioning
confidence: 99%